Bahasa Inggris - Siti Yahriyah; Rakhmawati; Titis Setyaningrum; Kholil Baidowi; Uswatun Khasanah (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to develop an ecotheological education model that can be applied in community-based cottage industries, specifically in the context of cattle waste management. By integrating Islamic values and environmental principles, this approach seeks to build ecological awareness and spiritual responsibility in organic waste management. The study was conducted through a qualitative approach using a case study method in a local cattle farming community that manages waste for fertilizer and alternative energy purposes. The results show that the application of Islamic ecotheological values, such as monotheism, khalifah, and amanah, can strengthen the community's motivation in maintaining a balance between economic needs and environmental sustainability. This model also serves as a transformative educational tool that encourages active community participation in sustainable resource management. This research contributes to the development of a contextual and applicable religious-values-based environmental education curriculum at the community level.